Opening the black box: dopamine, predictions, and learning - Eshel, Neir (2013)
Dopamine neurons are thought to promote learning by signaling prediction errors, that is, the difference between actual and expected outcomes. Whether these signals are sufficient for associative learning, however, remains untested. A recent study used optogenetics in a classic behavioral paradigm to confirm the role of dopamine prediction errors in learning.